Bioclimatic and Taxonomic Consequences of Tectonic Movement and Orogeny - Whyte, Robert Orr (Annals of Arid Zone, 2016)
Nine major periods arc recognized in the palaeoclimatic and recent history of the South Asian Subcontinent, associated with or created by the major geological events, the arrival of the South Asian Plate and the orogeny of Tibet, the Karakorum and the Himalaya. Only in the eighth and ninth Of these periods would conditions have begun to favour the dispersal and rapid speciation of the herbaceous vegetation remarkably young is the rich gramineous flora of the present day.